PENINGKATAN KEMAMPUAN BERMAIN PIANIKA MELALUI METODE DRILL DI SMP NEGERI1 LUBUK ALUNG PADANG PARIAMAN - Idati Idati; Jagar Lumban Toruan; Erfan Lubis (FBS Universitas Negeri Padang, 2014)
Abstract This research was designed for improving the students’ ability in playing Pianika by using Drilling Method in class VIII-7 of SMP Negeri 1 Lubuk Alung. This was a classroom action research wich was conducted in two cycles consisting of planning, acting, observing and reflecting. The object of the research was the students in class VII-7 of SMP Negeri 1 Lubuk Alung Kabupaten Padang Pariaman that consisted of 36 students. The result of the research indicated that from the first cycle to the second cycle, the use of Drilling Method could improve the students’ ability in playing Pianika. In addition, the students’ activities in the learning process also improved. Kata Kunci : Peningkatan, Pianika, Metode Drill